Fabrication and study of 2D NbOI2-based photovoltaic device - Goh, Yee Peng (Nanyang Technological University, 2024)
The generation of photocurrent in conventional photovoltaic cells is predominantly reliant on the interface of p-n junctions or Schottky barriers, with the photoelectric conversion efficiency being inherently limited by the Shockley-Queisser limit. Recent advancements, however, have demonstrated potential in surpassing this boundary via the employment of bulk photovoltaics of two-dimensional (2D) ferroelectric crystals devoid of inversion symmetry. The search for novel 2D ferroelectric material has never lose its momentum to find materials with better qualities for photovoltaic application. NbOI2 is one such material with the preceding quality after scientist scavenge through available database to predict a promising ferroelectric material. It has been theoretically confirmed that NbOI2 has stronger polarisation and smaller band gap compared with other ferroelectric perovskite thin film materials. Since NbOI2 is a new member of the 2D ferroelectric family, there have been few experimental studies on its basic properties and photovoltaic properties, which highlights the need for further exploration. In this project, we present a systemic study of the ferroelectric photovoltaic properties of NbOI2-based device. The in-plane ferroelectricity in NbOI2 was investigated by piezoresponse force microscopy (PFM) measurement. Based on that, the photovoltaic device will be fabricated using NbOI2 as the function layer to measure the photovoltaic effect. The suitable bandgap (1.95eV) of the NbOI2-based photovoltaic device enables it to have a tunable photovoltaic response, allowing for broader photoresponse regulation in the visible light range.